AN ANALYSIS OF INDONESIAN ELT TEXTBOOK TO PROMOTE MULTIMODAL COMMUNICATIVE SKILLS - Ilyas, Fitri Susanti (Universitas Lambung Mangkurat, 2024)
Developing students’ multimodal communicative competence is essential in the Indonesian new curriculum, Kurikulum Merdeka (Freedom Curriculum). To help achieve this goal, the Indonesian government created a series of textbooks. This study explored whether the textbooks have served their designated purpose by scrutinizing the representation of various modes used in the textbook and the methodological features to support the improvement of students’ multimodal communicative competence. One textbook, Work in Progress, was chosen to be analyzed using Littlejohn’s three-level evaluation framework. It was found that the book has incorporated combinations of modes in the form of input and expected outputs. However, the pedagogical aspect employed does not encourage the development of multimodal communicative competence.